Pharmaceutical chemistry : therapeutic aspects of biomacromolecules - Bladon, Christine M. (Chichester, England : Wiley & Sons, Inc., 2002)
Explores the way in which peptides, proteins, nucleic acids and carbohydrates use therapeutically. With help of illustrations, this book covers both compounds and how therapeutics exert their influence through an understanding of biological processes.
Introduction -- Endogenous peptides and proteins -- Modification of endogenous peptides and proteins -- The immune system -- Oligonucleotides -- Oligosaccharides -- Appendix.
Includes index.
Keywords: PHARMACEUTICAL CHEMISTRY